Effects of biliopancreatic diversion on diurnal leptin, insulin and free fatty acid levels. Issue 6 (23rd March 2015) - Raffaelli, M.; Iaconelli, A.; Nanni, G.; Guidone, C.; Callari, C.; Fernandez Real, J. M.; Bellantone, R.; Mingrone, G.
<x xml:space="preserve">Abstract</x> Background Free fatty acid (FFA) levels are raised in obesity as a consequence of increased production and reduced clearance. They may link obesity with insulin resistance. Bariatric surgery can result in considerable weight loss and reduced insulin resistance, but the mechanism of action is not well understood. Although drugs such as metformin that lower insulin resistance can contribute to weight loss, a better understanding of the links between obesity, weight loss and changes in insulin resistance might lead to new approaches to patient management. Methods Variations in circulating levels of leptin, insulin and FFAs over 24 h were studied in severely obese (body mass index over 40 kg/m2) women before and 6 months after biliopancreatic diversion (BPD). Body composition was measured by dual‐energy X‐ray absorptiometry. A euglycaemic–hyperinsulinaemic clamp was used to assess insulin sensitivity. Levels of insulin, leptin and FFAs were measured every 20 min for 24 h. Pulsatile hormone and FFA analyses were performed. Results Among eight patients studied, insulin sensitivity more than doubled after BPD, from mean(s.d.) 39·78(7·74) to 96·66(27·01) mmol per kg fat‐free mass per min, under plasma insulin concentrations of 102·29(9·60) and 93·61(9·95) µunits/ml respectively. The secretory patterns of leptin were significantly different from random but not statistically different before and after BPD, with the exception of the pulse height which was reduced after surgery. Both plasma insulin and FFA levels were significantly higher throughout the study day before BPD. Based on Granger statistical modelling, lowering of daily FFA levels was linked to decreased circulating leptin concentrations, which in turn were related to the lowering of daily insulin excursions. Multiple regression analysis indicated that FFA level was the only predictor of leptin level. Conclusion Lowering of circulating levels of FFAs after BPD may be responsible for the reduction in leptin secretion, which in turn can decrease circulating insulin levels. <boxed-text content-type="box" id="bjs9780-blkfxd-0001" position="anchor" orientation="portrait"> Surgical relevance Insulin resistance is a common feature of obesity and type II diabetes. These patients are also relatively insensitive to the biological effects of leptin, a satiety hormone produced mainly in subcutaneous fat. Biliopancreatic diversion, a malabsorptive bariatric operation that drastically reduces circulating lipid levels, improves insulin resistance independently of weight loss. The mechanism of action, however, has still to be elucidated. This study demonstrated that normalization of insulin sensitivity after bariatric surgery was associated with a reduction in 24‐h free fatty acid concentrations and changes in the pattern of leptin peaks in plasma. Bariatric surgery improves the metabolic dysfunction of obesity, and this may be through a reduction in circulating free fatty acids and modification of leptin metabolism. </boxed-text>